Simultaneous HPTLC Estimation of Omeprazole and Cisapride in Pharmaceutical Dosage Form - P. Godse, Vijaya; Bhosale, A.V.; M. Gowekar, Narendra; V. Kasture, Avinash (Asian Journal of Chemistry, 2010)
A simple, rapid, reproducible and economical high performance thin layer chromatographic method for simultaneous estimation of omeprazole and cisapride in capsule has been developed. It was performed on Kieselghur 60, F254 thin layer chromatographic plates using mobile phase comprising of propanol:toluene (1:3) and the detection was carried out at 276 nm showing Rf value 0.34 for omeprazole and 0.56 for cisapride. The calibration curve response was observed between 0.1- 0.4 μg for omeprazole and 0.075-0.2 μg for cisapride by height and area. The per cent drug estimated for omeprazole and cisapride from marketed formulation was found to be 99.63 ± 0.93, 102.82 ± 0.82 by height and 100.47 ± 1.40,103.71 ± 1.05 by area, respectively. The per cent recovery by height and by area was found to be 100.16 ± 2.21 and 98.53 ± 3.38 for omeprazole and 100.24 ± 1.20 and 99.66 ± 0.88 for cisapride. The method was validated with the determination of accuracy, precision, specificity, linearity detector response and ruggedness.